A Basis for Determining the Adequacy of Evaluation Designs - James R. Sanders; Dean N. Nafziger (The Evaluation Center at Western Michigan University, 2011)
Originally published as Paper #7, Occasional Paper Series, April, 1976 * This paper was prepared under contract support from the Alaska Department of Education to the Northwest Regional Educational Laboratory.